The Problem of Copyright and the Interpretation of Australian Contemporary Aboriginal Painting - Westhuizen van der, Valeria O. (Actual Problems of Theory and History of Art, 2025)
One of the essential problems of the contemporary painting by Australian aboriginal people is the interpretation of the meaning of their paintings. As soon as these paintings have sacred meaning and the artists strive to keep their rights for the use of certain subjects and ornaments, a special concept of multi-level interpretation of the aboriginal paintings had been created and implemented.
Keywords: copyright; interpretation; Australia; contemporary aboriginal painting